Linguistic means of creating an image of a person with intellectual disabilities in D. Keyes’s novel «Flowers for Algernon» - Olga Kanevska; Iryna Klymenko (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
Reproducing the speech portrait of a character in the text of a literary work is a difficult artistic task, especially for characters who have certain intellectual impairments and speech disorders, i.e. suffer from aphasia. The writer gives an authentic and detailed description of certain manifestations of aphatic syndromes in the character taking into account both language disorders and psychopathological manifestations that significantly affect the structure and content of the text.